Common mistakes in statistical and methodological practices of sport management research - Kim, Y.; Lee, J. L. (Measurement in Physical Education and Exercise Science, 2019)
The purposes of this manuscript are to identify common statistical mistakes in sport management, and to provide scholars with suggestions on how to develop and improve the quality of quantitative research. We have reviewed articles published from 2001 to 2017 in the Journal of Sport Management, Sport Management Review, European Sport Management Quarterly, and International Journal of Sports Marketing and Sponsorship. We also discussed common mistakes found in the manuscripts we reviewed for publication in journals listed above. Among the many major and minor mistakes found in the sport management research, we classified the common mistakes that researchers (and/or journal reviewers and editors) often commit into three broad categories: pre-, peri-, and post-analysis mistakes.